2023
DOI: 10.3390/su15076028
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Research in Times of COVID-19: Experiences from South America

Abstract: The pandemic caused by COVID-19 has had diverse effects on the population and businesses. Due to their low visibility, there is a significant knowledge gap for the scientific community regarding the situation of South American entrepreneurship during the COVID-19 pandemic. Therefore, this systematic review aims to answer the following research questions: What scientific evidence is available on entrepreneurship in South America during the COVID-19 pandemic? From which countries do the studies originate? What c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 124 publications
0
6
0
2
Order By: Relevance
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurship and self-employment in South America showed great resilience, with the ability to virtualise their business, suggesting that the economic stability of employees and their communities is as important as the business itself [8]. Evidence from the top 10 affected countries showed that financial asset markets suffered, while real asset markets remained more stable, with trade and travel affecting the oil market [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to changing conditions, many entrepreneurs have redirected their operations toward new markets. Previous studies have underscored that entrepreneurs who managed to adapt to these new ecosystem rules and targeted their businesses toward new markets were able to survive the crisis and maintain their market positions [27][28][29][30].…”
Section: Entrepreneurial Adaptation and Crisis Managementmentioning
confidence: 99%
“…During the COVID-19 confinement, as sales were affected, some companies neglected to maintain constant communication or foster relationships with their customers. It is known that during those times, many ventures had to change the way they conducted business [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%